RANCANG BANGUN APLIKASI PENERIMAAN PESERTA DIDIK BARU PADA PAUD TUNAS MAWAR MENGGUNAKAN METODE WATERFALL DAN EVALUASI USABILITY DENGAN SYSTEM USABILITY SCALE - Audrey Winiyaah; Muhammad Patria (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
PAUD Tunas Mawar is developing a web-based new student admission application using the waterfall method with primary technologies PHP and MySQL. This application is designed to address the challenges of manual data processing, which is prone to archival loss and inefficiency. The system has been tested using the SDLC software development model to ensure adequate technological readiness. Based on the results of testing with the System Usability Scale (SUS), this application achieved grade A with a final score of 81.8, indicating that the application has met user needs. The results of questionnaires distributed to 18 respondents, including administrators, teachers, and prospective students, suggest that this application is expected to enhance efficiency, transparency, and the quality of educational services at PAUD Tunas Mawar, providing significant benefits in the new student admission process.